Measuring the Structural Quality of Software Systems. - Curtis, Bill; Martin, Robert A.; Douziech, Philippe-Emmanuel; Mariani, Riccardo (Computer (00189162), 2022)
The International Organization for Standardization recently published ISO/IEC 5055:2021 for measuring the reliability, security, performance efficiency, and maintainability of software systems by detecting and counting severe violations of good architectural and coding practice.